Development of a Prototype of a Protective UV-C Half-Face Mask with Implementation of Additive Technology - Varecha, Daniel; Galik, Jan; Brumercik, Frantisek; Kohar, Robert; Madaj, Rudolf; Drbul, Mario; Glowacz, Adam; Glowacz, Witold; Liu, Hui (Communications - Scientific Letters of the University of Zilina, 2023)
The authors of this manuscript present development of a prototype protective UV-C half-face mask. The first stage of this study focuses on proposing a UV-C half-face mask design and the second phase investigates the quality of printings, 3D/2D roughness and porousness of three different printed samples of PA12. Development of the protective half-face mask used the non-destructive technology of 3D scanning of the human body by the Ein Scan scanner. As a part of the experiment, three samples were prepared with Sinterit Lisa, EOS Formiga and HP jet fusion printers. SLS and MJF technology were used during the experiment. The experimental observation of the structure of the surface was secured using the Alicona Infinite focus G5 device. The conclusions present the study's results and the authors' recommendations for other developers dealing with the development of the protective face masks.
Keywords: rapid prototyping; photogrammetry-3D projection additive manufacturing; 2D/3D roughness of PA12; selective laser sintering (SLS) multi-jet fusion (MJF)